The Living Politics of Self-Help Movements in East Asia (Springer Singapore, 2018)
This collection elucidates the complexity of living politics in the 21st century, considering how self-help groups draw on shared regional traditions, and how they adapt their actions to the diverse formal political environments in which they operate. It considers the nexus between ideas and action in a world where the conventional 'right-left' divide has a decreasing hold on the political imagination. Examining grassroots self-help actions as responses to everyday life problems, it argues that whilst action may be initiated by encounters with ideas that come into the community from outside, often the flow of cause and effect works in the opposite direction. Focusing on countries both politically dynamic and with long-standing historical and cultural connections - China (including Inner Mongolia), Japan, Taiwan and Korea - this book fills a significant gap in the literature on social movements, demonstrating that survival itself is a political act.